Terapi antibiotika empiris pada neonatus - Muchtar Kusuma Hayatullah; Guslihan Dasa Tjipta; Pertin Sianturi; Emil Azlin; Bugis Mardina Lubis; Syamsidah dr; Fera Wahyuni (Fakultas Kedokteran USU, 2017)
Neonatal sepsis is a clinical syndrome with symptoms of systemic infection and followed by bacteremia in the first month of life. Antibotic initial therapy empirically is often given concomittantly awaiting the results of blood cultures in neonates with suspected sepsis. The recommended initial treatment in general is a combination of ampicillin and aminoglycoside (gentamicin). Alternative to aminoglycosides is the third-generation cephalosporins (eg cefotaxime). This regimen was found safe and effective by appropriate duration of therapy. This therapy should be evaluated every 48 hours with a lingering risk of therapy associated with increased risk of necrotizing enterocolitis and death.Keyword : antibotic initial, Neonatal sepsis